Investigating Policyholders’ Perception Towards Insurance: Evidence From Structural Equation Modeling - Lawaju, Purnima; Awale, Prakriti; Basyal, Devid Kumar; Thakur, Abhishek; Bhandari, Anil; Paudel, Udaya Raj (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: Within the burgeoning insurance market of the Kathmandu Valley, this study aims to investigate the perceptions of policyholders regarding insurance. It seeks to understand the factors influencing policyholders and propose solutions to the challenges faced in the insurance industry. Methodology: This study employs a cross-sectional survey methodology, utilizing non-probability sampling, and specifically purposive sampling, to collect data from the insurance policyholders of Kathmandu Valley. Structured questions were used to elicit responses from a sample of 403 participants. For data analysis both descriptive and inference statistics were used. Findings and Conclusion: Findings of the study reveal that policyholders perceive insurance policies as essential safeguards against financial risks. However, several challenges, including policy misunderstanding, claim denials, and policy complexity, were identified. Through structural equation modeling, significant relationships between Customer Loyalty and Transparency with policyholders’ perceptions was observed. Implications: The study contribute to enhance policyholders’ understanding and perception of insurance, thereby fostering trust and satisfaction in the insurance industry